Collaboration Between Actors in Prevention of Terrorism: A Study of the Involvement of Former Terrorist Convicts with the TNI in Deradicalization Activities in the TNI Manunggal Development Village Program - Khitam, Muhammad Chusnul (Journal of Governance and Administrative Reform, 2023)
Abstract Collaboration between actors is needed for deradicalization programs, not only between institutional (institutional) actors but actors outside institutions need to be involved in the deradicalization process as a form of national resilience. This article discusses the involvement of former terrorist convicts (Napiters) who are members of the Circle of Peace Foundation (YLP) and the TNI (Indonesian National Army) in efforts to deradicalize the process through the TNI Manunggal Pembangunan Desa (TMMD) program. This research was conducted with the object of ex-terrorist convicts by conducting interviews, documentation studies, and observations. The analysis of this research uses a collaborative governance theory approach as an analytical knife with qualitative research methods. Keywords: Actor collaboration, TNI, former terrorist convicts, deradicalization Abstrak Kolaborasi antar aktor diperlukan untuk program deradikalisasi, tidak hanya antar aktor institusional (kelembagaan) tetapi aktor diluar kelembagaan perlu dilibatkan untuk proses deradikalisasi sebagai wujud ketahanan nasional. Tulisan ini membahas tentang pelibatan mantan narapidana teroris (Napiter) yang tergabung dalam Yayasan Lingkar Perdamaian (YLP) dan TNI (Tentara Nasional Indonesia) dalam upaya proses deradikalisasi melalui program TNI Manunggal Membangun Desa (TMMD). Penelitian ini dilakukan dengan obyek mantan narapidana teroris dengan melakukan wawancara, studi dokumentasi dan observasi. Analisa penelitian ini dengan pendekatan teori collaborative governance sebagai pisau analisis dengan metode penelitian kualitatif. Dari penelitian ini ditemukan bahwa sinergitas antara TNI dengan mantan narapidana teroris harus secara terpadu dan terintegrasi untuk proses deradikalisasi melalui program pelaksanaan TMMD sehingga terwujudnya ketahanan nasional. Kata kunci: Kolaborasi aktor, TNI, mantan narapidana teroris, deradikalisasi.